The Music of Memory Gaston Bachelard on the Construction of Time and Memory (Itinera, 2024)
Gaston Bachelard's philosophical exploration challenges conventional assumptions regarding the relationship between time and memory. Departing from the common perception of time as a passive container for memories, Bachelard introduces an idea of the past that is predicated on a relational understanding of time. This paper will begin by contrasting Bachelard's relational view of time with Henri Bergson's substantivalist stance. Bachelard's metaphysical position on time provides the conceptual groundwork for his challenging of the fixity of past temporal experiences, and his redefining of duration as a rational construct. Finally, this paper will explore Bachelard’s concept of rhythmanalysis, or the process by which the individual is able to make sense of the different rhythms or frequencies of time. Bachelard does not define the past as a fixed temporal series of memories. Rather, memories and the past are fluid and continually open to interpretation by the individual. The relationship between time and memory, for Bachelard, is subsequently predicated on a constructive process which is characterized by the ability of the individual to reframe or reinterpret that process.
Keywords: Gaston Bachelard, philosophy of time, philosophy of memory, rhythmanalysis.